PERAN KOMUNIKASI BISNIS DALAM STRATEGI BISNIS - Riefky Krisnayana (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
Employers should strive to close the gap that lies between the producer with the consumer society as a buyer or user of goods and services produced. Duties and responsibilities as an entrepreneur to always be able to influence the level of demand for goods production company, always trying to find a buyer produces. As a businessman he had to preach penyempurnaan- production improvements that have been dicapinya, where the goods are produced can be obtained consumer society. Providing communication with the market, is an absolute requirement for any manufacturer who produce large-Basaran shown to consumers who are not familiar. Implementation of communication with the market could also be called an absolute requirement for employers who want to ensure the viability of the company and move to develop. In the business environment there are various means of business communications that can be used employers to communicate with consumers. Means of communication available trading Pengirimin among others in the form of a letter, delivery wire, telephone conversations, personal visits.